Sistem Manajemen Asset Peralatan Dengan Standart Mutu Berbasis Teknologi Informasi - Didik Nugroho (STMIK Sinar Nusantara, 2011)
Very important asset for an organization or institution. Because with this asset of an organization or institution can be assessed level of success. One form of asset is the asset equipment. Asset equipment is a tool used by institutions to achieve its objectives. So for the equipment assets to support performance management institution needs to be done with good management. Equipment assets to be managed by applying a standard of quality that will support the activities of an institution. Optimal asset management process in order to take advantage of information technology. Information technology has been widely applied in such institutions in financial management. Utilization of information technology has improved optimization agency.Keyword: Manajmen assets, Quality Management, Information Technology.